Engineering of membrane phospholipid component enhances salt stress tolerance in Saccharomyces cerevisiae. Issue 3 (9th January 2020) - Yin, Nannan; Zhu, Guoxing; Luo, Qiuling; Liu, Jia; Chen, Xiulai; Liu, Liming
Abstract: To increase the growth of industrial strains under environmental stress, the Saccharomyces cerevisiae BY4741 salt‐tolerant strain Y00 that tolerates 1.2 M NaCl was cultured through nitroguanidine mutagenesis. The metabolomics and transcription data of Y00 were compared with those of the wild‐type strain BY4741 . The comparison identified two genes related to salt stress tolerance, cds1 and cho1 . Modular assembly of cds1 and cho1 redistributed the membrane phospholipid component and decreased the ratio of anionic‐to‐zwitterionic phospholipid in strain Y03 that showed the highest salt tolerance. Therefore, significantly increased membrane potential and membrane integrity helped strain Y03 to resist salt stress (1.2 M NaCl). This study provides an effective membrane engineering strategy to enhance salt stress tolerance. Abstract : Cell membrane is the natural barrier separating the extracellular and intracellular environment. In this study, a membrane engineering strategy by altering membrane phospholipid component to enhance Saccharomyces cerevisiae salt stress tolerance was developed. Due to the redistribution of membrane phospholipid, membrane functions were changed to resist salt stress. This strategy described here enhances tolerance and robustness of industrial strains, which may consequently improve the efficiency of microbial cell factories.